BAJRA SANDHI: MONUMEN PERJUANGAN RAKYAT BALI SUMBANGAN TERHADAP TEGAKNYA KEDAULATAN NEGARA KESATUAN REPUBLIK INDONESIA - Ida Bagus Brata (Jurnal Santiaji Pendidikan (JSP), 2014)
Bali as one of the battle ground against the colonizer holds many historic value. To commemorate the patriots’ virtue that was given for Indonesia, a monument called Bajra Sandhi was built. There are archieves about the virtues of Balinese patriots before and after the Independence Day. The monument is expected to give benefits for the sake of improving appreciation of the young generations in experiencing patriotic values that are inherited. The monument is the identity and the symbol of togetherness and as a media of communication between the post generations to the next generation. The track records of the patriots that are documented are a kind of guidance in developing and preserving the unity of the nation for the future.